Current pool of ultimate collection of mitochondrial DNA from remnants of Kalash - Muhammad Hassan Siddiqi; Allah Rakha; Khushbukhat Khan; Tanveer Akhtar (Mitochondrial DNA. Part B. Resources, 2021)
The mitochondrial DNA (mtDNA) complete control region coverage of 111 individuals from Kalash population of Pakistan has been presented for forensic applications and to infer their genetic parameters. We detected in total 14 different haplotypes with only five unique and nine shared by more than one individual. This population has come up with quite lower haplotype diversity (0.8393) and very higher random match probability (0.1682), and ultimately lower power of discrimination (0.832). Additionally, haplogroup distribution reveals the genetic ancestry of Kalash, mainly from West Eurasia (98.8%) and very little from South Asia (0.9%). Neither African lineages nor East Asian genetic segments were detected among these Kalash. This study will contribute to the database development for forensic applications as well as to track the evolutionary highlights of this ethnic group.